Sandostatin therapy in patients with chronic sarcoidosis - Timmermans, Wilhelmina MC; van Laar, Jan AM; Dalm, Virgil ASH; Kam, Boen LR; van Hagen, P Martin; van Daele, Paul LA (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2018)
Not available